§2.3 The Chain Rule and Higher Order Derivatives

Embed Size (px)

DESCRIPTION

§2.3 The Chain Rule and Higher Order Derivatives. The student will learn about. composite functions,. the chain rule, and. nondifferentiable functions. Composite Functions. Definition. A function m is a composite of functions f and g if - PowerPoint PPT Presentation

Text of §2.3 The Chain Rule and Higher Order Derivatives

  • *2.3 The Chain Rule and Higher Order DerivativesThe student will learn aboutcomposite functions, the chain rule, andnondifferentiable functions.

  • *Composite Functions Definition. A function m is a composite of functions f and g if m (x) = f g = f [ g (x)]This means that x is substituted into g first. The result of that substitution is then substituted into the function f for your final answer.

  • *ExamplesLet f (u) = u 3 , g (x) = 2x + 5, and m (v) = v. Find: f [ g (x)] = g [ f (x)] =g (x3) = m [ g (x)] = f (2x + 5) =(2x + 5)3m (2x + 5) = 2x 3 + 5 2x + 5

  • *Chain Rule: Power Rule. We have already made extensive use of the power rule with xn, We wish to generalize this rule to cover [u (x)]n, where u (x) is a composite function. That is it is fairly complicated. It is not just x.

  • *Chain Rule: Power Rule. That is, we already know how to find the derivative of f (x) = x 5We now want to find the derivative of f (x) = (3x 2 + 2x + 1) 5What do you think that might be?

  • * General Power Rule. [Chain Rule]If u (x) is a function, n is any real number, andIf f (x) = [u (x)]nthenf (x) = n un 1 uor* * * * * VERY IMPORTANT * * * * *Chain Rule: Power Rule.

  • *ExampleFind the derivative of y = (x3 + 2) 5.Let the ugly function be u (x) = x3 + 2. Then5(x3 + 2)3x24= 15x2(x3 + 2)4

  • *ExamplesFind the derivative of:y = (x + 3) 2 y = 2 (x3 + 3) 4 y = (4 2x 5) 7y = 7 (4 2x 5) 6 (- 10x 4)y = 2 (x + 3) (1) = 2 (x + 3) y = - 8 (x3 + 3) 5 (3x 2) y = - 70x 4 (4 2x 5) 6y = - 24x 2 (x3 + 3) 5

  • *ExampleFind the derivative of y =Rewrite as y = (x 3 + 3) 1/2 = 3/2 x2 (x3 + 3) 1/2Then y = 1/2Then y = 1/2 (x 3 + 3) 1/2Then y = 1/2 (x 3 + 3) 1/2 (3x2)Try y = (3x 2 - 7) - 3/2 y = (- 3/2) (3x 2 - 7) - 5/2 (6x)= (- 9x) (3x 2 - 7) - 5/2

  • *ExampleFind f (x) if f (x) = We will use a combination of the quotient rule and the chain rule.Let the top be t (x) = x4, then t (x) =4x3Let the bottom be b (x) = (3x 8)2, then using the chain rule b (x) = 2 (3x 8) 3 =6 (3x 8)

  • *Remember Def: The instantaneous rate of change for a function, y = f (x), at x = a is: This is the derivative.Sometimes this limit does not exist. When that occurs the function is said to be nondifferentiable.

  • *Remember Def: The instantaneous rate of change for a function, y = f (x), at x = a is: This is the derivative and a graphing way to represent the derivative is as the slope of the curve. This means that at some points on some curves the slope is not defined.

  • *Corner point

  • *Vertical Tangent

  • *Discontinuous Function

  • *"If a function f "

  • *Summary. Ify = f (x) = [u (x)]nthenNondifferentiable functions.

  • *ASSIGNMENT2.3 on my website11, 12, 13.

Recommended

View more >